Barodiffusion effects in bifurcating capillaries - Chavarría-Krauser, Andrés; Jäger, Willi (Computing and visualization in science, 2010)
For a dissolved compound, a stationary transport equation containing a barodiffusion term is obtained. The compound distribution is approximated for the case of a network of thin pipes, and is given by the first non-harmonic pressure approximation term. Numerical simulations of the compound distribution and its approximation are considered for the case of two simple two-dimensional domains. The proposed equation is able to describe inhomogeneities in the stationary compound distribution between the branching vessels. Further, the approximation sufficiently describes the inhomogeneities.
Published online: 20 December 2009
Gesehen am 17.08.2018